2002
DOI: 10.1002/1521-4109(200202)14:3<186::aid-elan186>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Structure of Lariat Crown Ethers for Ion-Selective Electrodes: Significant Shifts in Sodium/Potassium Selectivity

Abstract: Lariat crown ethers (LCEs) offer the ability to bind selectively alkali metal ions. The presence of a coordinating functionality in the sidearm chain provides a means to further tune the selectivity of LCEs. A series of four LCEs based on a 15‐crown‐5 structural motif were synthesized with variations in the coordinating functionality of the sidearm and the substitution at the carbon pivot atom. Poly(vinyl chloride) liquid‐membrane ion‐selective electrodes were prepared with each of the four ionophores, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…This immediately suggests that the ion-water interaction is progressively weakened going from the [0,4] to the [3,1] species. With Na + , the ν asym transition shifts from 3725 cm -1 in the [0,4] cluster ion to 3742 cm -1 in the [3,1] cluster ion. The change in the ν sym transition is not as dramatic, but is still detectable: the frequency shifts from 3645 to 3654 cm -1 going from [0,4] to [3,1].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This immediately suggests that the ion-water interaction is progressively weakened going from the [0,4] to the [3,1] species. With Na + , the ν asym transition shifts from 3725 cm -1 in the [0,4] cluster ion to 3742 cm -1 in the [3,1] cluster ion. The change in the ν sym transition is not as dramatic, but is still detectable: the frequency shifts from 3645 to 3654 cm -1 going from [0,4] to [3,1].…”
Section: Resultsmentioning
confidence: 99%
“…With Na + , the ν asym transition shifts from 3725 cm -1 in the [0,4] cluster ion to 3742 cm -1 in the [3,1] cluster ion. The change in the ν sym transition is not as dramatic, but is still detectable: the frequency shifts from 3645 to 3654 cm -1 going from [0,4] to [3,1]. These trends are identical with those of K + .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, while most macrocycles containing hard oxygen centers demonstrate selectivity toward alkaline and alkali earth cations, crowns containing softer sulfur atoms tend to interact with softer species like transition-metal ions. Macrocycle selectivity can also be tuned by adding side arm functionalities, or "lariats", to the molecular frame, which can lend stabilizing interactions with various cations or alter binding through steric blockage of the crown cavity [4,107,108,109]. Of equal importance to acid-base chemistry, however, is the overall size or diameter of the binding area.…”
Section: Cation-binding Ionophoresmentioning
confidence: 99%
“…25 Lariat ethers have also been reported to bind alkali cations and behave as ionophores in bulk liquid membranes and ion-selective electrodes. [26][27][28][29] The dialkylated diaza(18-crown-6) ethers, a subset of the lariat class, have been reported to have toxic activity towards prokaryotic and eukaryotic cells. 20 Evidence from toxicity and depolarization assays initially suggested that these compounds behave as ion carriers.…”
mentioning
confidence: 99%
“…Binding to ionophores requires at least a partial substitution of water molecules in the hydration sphere by ions to achieve an ionophore-like transport mechanism. Thus, some degree of ion selectivity is expected, [26][27][28][29] as observed in the case of valinomycin, a natural carrier-type ionophore that is extremely selective for K + over Na + 39,40 and does not transport N-methyl-D-glucamine (NMDG + ). When depolarization assays were performed in the presence of different cations, valinomycin promoted DiSC 3 (5) release only when K + was added to the external solution, but not when Na + or NMDG + was added ( Fig.…”
mentioning
confidence: 99%